Literasi Digital Pemuda dalam Konteks Pemberdayaan Masyarakat di era Society 5.0 - Dudi Setiadi; Sri Nurhayati; Ansori Ansori; Mohamad Zubaidi; Rudi Amir (Society, 2023)
The purpose of this study is to determine the level of digital literacy among the member of youth organization (commonly called Karang Taruna) of Cicau Hamlet, Gadobangkong Village, Ngamprah Sub-district, West Bandung Regency, West Java Province, Indonesia, focusing on the use of the Internet in the context of community empowerment in the fields of self-development and economy. Case study methodology is employed, with data gathering approaches consisting of in-depth interviews, documentation studies, and observations of fifteen (15) Karang Taruna member informants. The findings of the study indicate that: The youth digital literacy in computer operation and Information and Communication Technology (ICT) abilities in the internet area are fairly strong, but there is still opportunity for improvement through enhancing infrastructure for stable internet connections and educating youth about the most recent ICT advances. When it comes to creating digital products in a variety of formats and models, youth have a low degree of digital literacy. This is due in part to a lack of imagination and creative thinking skills among digital content creators. Youth require continual training to increase their digital literacy and ability to create various types of digital material, which will contribute to the expansion of Indonesia’s creative economy sector. Youth digital literacy must be improved in terms of their ability to collaborate in the digital space, and education about collaboration must be conducted in accordance with digital ethics and security so that the youth of the Indonesian nation can collaborate with respect and remain safe from cybercrime. Youth still lack the digital literacy necessary to pick and filter legitimate and hoax-free content. Digital literacy pertaining to the ability to use digital technology for youth economic empowerment is included in the category of lacking because youth are still not literate and digitally proficient in using digital technology to increase income, raise their economic level through business opportunities in the digital space, and use digital wallets for sales transactions. Youth digital literacy in relation to self-development is also still weak and must be focused to add insight into access to information in the digital realm for career development and self-potential. As well as the usage of communities that are favorable to youth growth and self-healing. This study recommends intensive training and assistance for youth in digital content creation, as well as financial literacy education related to capital management and digital-based creative economy business opportunities.